Investigation On Human Trafficking Especially Women - Vinorika Padmadayani; Lathifah Hanim (Law Development Journal, 2020)
This study aims to identify and analyze the implementation of investigations the criminal act of human trafficking, especially women at the Brebes Police, what affects the rampant of human trafficking human trafficking, the factors that hinder and solutions in the implementation of the investigation of human trafficking, especially women in Brebes Police. This research uses an empirical juridical approach with descriptive analysis research specifications. The data used are primary data and secondary data obtained through interviews and literature study. The data analysis method used was qualitative analysis. Furthermore, based on the research results it can be concluded; The investigation of the criminal act of human trafficking is in accordance with the Criminal Code, but the investigators of the PPA Unit at the Brebes Police found a problem, namely that the laws and policies regarding human trafficking have not been properly socialized. The poverty factor, the desire to get rich quick, and the habitual factors of the population that become a culture,